Food Consumption Behaviors and Non-Communicable Diseases among Urbanized Medical Personnel - Benyapad, Pirunnapa; Wongrostri, Yupa; Podjamanpong, Pattarasiri; Trongtrakul, Konlawij; Phairatwet, Piyarat (Journal of The Royal Thai Army Nurses, 2023)
This study aimed to compare the differences in food consumption behavior (FCB) with noncommunicable diseases from a sample of 412 medical staff who work in an urbanized area (353 person) and those in non-urbanized (59 person). The populations were selected by stratified sampling method. The FCB questionnaire, previously used in the study by family members of the officers of Phramongkutklao Hospital, was applied for our study. The questionnaire had good reliability in our study, with Cronbach’s Alpha coefficient at 0.86. Statistical analyses in our study including frequency, percentage, mean and standard were used for the descriptive data; independent t-tests and Fisher exact tests were used for the analytical part. The FCB was divided into 3 levels: good, moderate, and should be improved. The results of our study demonstrated that FCB was associated with a risk of several chronic diseases such as hypertension, chronic kidney disease, cancer, diabetes, and obesity among staff in the Faculty of Medicine Vajira Hospital (urbanized area) and Somdet Phra Sangharaja-19 Hospital (non-urbanized area). Comparing the percentage of each aspect by considering the frequency of practice, it was found that the staff of the two centers did not differ significantly with statistical significance (P<0.05). There was no significantly different in the overall behavior of the staff between centers. The overall score in the Faculty of Medicine Vajira Hospital (urbanized area) and Somdet Phra Sangharaja-19 Hospital (non-urbanized area) were x = 3.11, SD=0.88vs. x=3.18, SD=0.95, respectively, However, in terms of However, in terms of eating grilled food, including meatballs, pork, chicken, and fish was significantly different between centers, with all (P<.05). In summary, FCB according to consumerism among medical staff from urban and non-urban are still had a risk for chronic diseases. Therefore, the consumption behaviors should be research studies other for plan to promote or encourage personnel to have good consumption behaviors to prevent non-communicable diseases and enhance good health.